Strategic CSR for innovation in SMEs: Does diversity matter?. Issue 6 (December 2019) - Bocquet, Rachel; Le Bas, Christian; Mothe, Caroline; Poussing, Nicolas
Abstract: Both corporate social responsibility and diversity influence firms' innovation, yet their relationship and links to innovation remain uncertain, especially among small to medium-sized enterprises. Relying on strategic and institutional CSR perspectives and a value-in-diversity approach, this study examines the mediating roles of gender and nationality diversity on the CSR–innovation link at the organizational level. With a sample of 1348 SMEs from Luxembourg, the results show that strategic CSR can promote both types of diversity, but only nationality diversity triggers technological innovation. Nationality diversity emerges as a partial mediator of the relationship between CSR and SMEs' technological innovation. Thus, strategic CSR, through the genuine pursuit of such diversity, can help SMEs attain positive returns on their product or process innovation. These results have important theoretical and managerial implications.